Pterostilbene inhibits lung squamous cell carcinoma growth in vitro and in vivo by inducing S phase arrest and apoptosis - Tan, Kok‑Tong; Chen, Ping‑Wen; Li, Shiming; Ke, Te‑Min; Lin, Sheng‑Hao; Yang, Ching‑Chieh (Oncology letters, 2019)
Natural dietary components have become the subject of an increasing amount of interest due to the side effects of anticancer treatment. Pterostilbene, an analog of resveratrol, is primarily found in grapes, and has been suggested to exert antioxidant and anticancer effects in different tumor types. The present study aimed to investigate the antitumor effects and molecular mechanisms of pterostilbene in the human lung squamous cell carcinoma (SqCC) cell line, H520. The results of the present study indicate that pterostilbene significantly reduced cell viability and induced S phase arrest, and that treatment with pterostilbene was associated with the downregulation of cyclin A and cyclin E, as with the upregulation of p21 and p27 expression in H520 cells. In the apoptosis analysis, pterostilbene induced S phase accumulation and the activation of caspase-3, -8 and -9 in H520 cells, potentially through the activation of extrinsic and intrinsic apoptotic pathways. Additionally, the study demonstrated that pterostilbene effectively inhibited lung SqCC growth in a H520 ×enograft model. Given the and antitumor effects of pterostilbene demonstrated in the present study, pterostilbene may serve a novel and effective therapeutic agent to for patients with SqCC.